BELAJAR DARI CILACAP: KEBIJAKAN REFORMA AGRARIA ATAU REDISTRIBUSI TANAH - Heri Setiaji; Deden Dani Saleh (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
The Agrarian Reform or The Program of National Renewal Reform on Agrarian Affairs was carried out in 2007. Bythe implementation of the program, the agrarian structure which used to be unbalanced was expected to be balanced and just.By the new structure it was hoped that the poverty in villages and problems of peasants’ welfares could be overcome. However,the implementation of the policy was still considered as not fulfilling the people’s hopes. The research was aimed at describingthe agrarian reform using the site approach. This resulted on the failure of the new agrarian structure and superficially orientedon solving the conflicts.Key words: agrarian reform, policy implementation